Land-use determines the distribution of large branchiopods in climatically homogeneous northern Pannonia - Alžbeta Devánová; Jan Sychra; Johannes Wessely; Franz Essl; Andrej Mock; Michal Horsák; Tobias Schernhammer (Global Ecology and Conservation)
Large branchiopods are key biota of temporary pools in Central European lowlands. Due to land use changes, they are among the most threatened aquatic invertebrates in Europe. The lack of information on the main drivers of species distribution hinders effective protection and conservation prioritisation. We selected eight branchiopod species with representative data on their occurrence in the northern Pannonia to identify the most important drivers of their distribution and to predict their distribution in unexplored temporary pools across the Pannonian region of southern Slovakia, south-eastern Czech Republic, and eastern Austria. Data on pool size and isolation, soil characteristics, land use and climate were used to generate species distribution models using five modelling techniques and ensemble predictions. The distribution of species was mainly affected by the proportion of arable land within the pool (e.g. Triops cancriformis, Leptestheria dahalacensis), land use (e.g. Eubranchipus grubii, Lepidurus apus) and distance from the river (e.g. Branchinecta ferox and Chirocephalus carnuntanus). Wetland size and habitat isolation were also important for some species, mainly for Branchipus schaefferi and Imnadia yeyetta, respectively. As we focused on a climatically homogeneous area, climatic conditions only had the most important effect on the distribution of species that have their distribution limit in northern Pannonia (B. ferox, C. carnuntanus, I. yeyetta). Overall, the diversity of large branchiopods increased with pool size, while decreased with distance to a river and habitat isolation. As some distribution patterns emerged repeatedly in the models, the effective protection can be simplified to consider species that require contrasting conditions. Particular attention should be paid to ephemeral wetlands on arable land, crucial habitats for large branchiopods, yet lacking any protection. Our results can contribute to better conservation of large branchiopods by facilitating surveys of species in understudied areas and improving the knowledge on the species environmental niches.